2019
DOI: 10.1002/jsfa.9687
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the profiling of bioactive components with the roasting process in Lycium chinense leaves and the anti‐obesity effect of its bioaccessible fractions

Abstract: BACKGROUND: This study aimed to investigate the profiles of bioactive components in roasted Lycium chinense leaves (LCLs) and its in vitro anti-obesity activity after digestion processes. RESULTS: Chlorogenic acid, kaempferol-3-sophoroside-7-glucoside, kaempferol-3-sophoroside, and kaempferol-3-glucoside were discovered as bioactive components in various ratios of ethanol (EtOH) extract in LCLs by using ultra-performance liquid chromatography-electrospray ionization-mass spectrophotometry (UPLC-ESI-MS). The ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Obesity can lead to an increase in body fat, especially with abdominal obesity that progresses to cytokine inflammation and insulin resistance in adipose tissue (Liu et al, 2021). Choi et al (2019) found a significant increase in glycosylated kaempferol in LCL after the roasting process with 30% EtOH as extractant. The roasted LCL contained abundant bioactive components, including kaempferol-3-sophoroside-7-glucoside, kaempferol-3sophoroside and kaempferol-3-glucoside, which converted into the potential natural regulators of adipogenesis-related factors in adipocytes, such as kaempferol and kaempferol-7-glucoside after digestion by human digestive enzymes.…”
Section: Anti-obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity can lead to an increase in body fat, especially with abdominal obesity that progresses to cytokine inflammation and insulin resistance in adipose tissue (Liu et al, 2021). Choi et al (2019) found a significant increase in glycosylated kaempferol in LCL after the roasting process with 30% EtOH as extractant. The roasted LCL contained abundant bioactive components, including kaempferol-3-sophoroside-7-glucoside, kaempferol-3sophoroside and kaempferol-3-glucoside, which converted into the potential natural regulators of adipogenesis-related factors in adipocytes, such as kaempferol and kaempferol-7-glucoside after digestion by human digestive enzymes.…”
Section: Anti-obesitymentioning
confidence: 99%
“…Interestingly, the chlorogenic acid content of LCL was elevated after infection by gall mite indicating a higher pharmaceutical or nutraceutical value of the galled leaves (Chen et al ., 2020). Moreover, the chlorogenic acid content of LCL was significantly affected by roasting which could appear only when using the particular aqueous ethanol (50%) as the extraction solvent (Choi et al ., 2019).…”
Section: Phytochemicals In Goji Leavementioning
confidence: 99%
“…In Western countries, goji berries can be considered a food since they are added to make baked goods and mix in cereal and yogurt. It has been reported that the fruit, root bark, and leaves of goji contain functional components. The polysaccharides isolated from the aqueous extracts of goji fruit have been identified as one of the major active ingredients responsible for multiple bioactivities.…”
Section: Introductionmentioning
confidence: 99%